2010
DOI: 10.1186/1471-2407-10-225
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia increases the metastatic ability of breast cancer cells via upregulation of CXCR4

Abstract: BackgroundChemokine SDF1α and its unique receptor CXCR4 have been implicated in organ-specific metastases of many cancers including breast cancer. Hypoxia is a common feature of solid tumors and is associated with their malignant phenotype. We hypothesized that hypoxia would upregulate CXCR4 expression and lead to increased chemotactic responsiveness to its specific ligand SDF1α.MethodsThree breast cancer cell lines MDA-MB-231, MCF7 and 4T1 were subjected to 48 hrs of hypoxia or normoxia. Cell surface receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 48 publications
7
55
1
5
Order By: Relevance
“…The increase in migratory ability due to hypoxia was abrogated by knockdown of HIF-1α and inhibition of CXCR4. These results are in accordance with previous reports in different types of cancer (16,46) and suggest that upregulation of CXCR4 by HIF-1α in response to hypoxia plays a biological role in gastric cancer cell migration. We previously reported that functional CXCR4 plays an important role in cancer cell migration during normoxia in gastric and gallbladder cancers (18,21), suggesting that the CXCR4/ CXCL12 axis may be significantly involved in cancer progression and may be a potential target for therapeutics that block the interaction between CXCL12 and CXCR4, or that inhibit downstream signaling, in the treatment of cancer.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The increase in migratory ability due to hypoxia was abrogated by knockdown of HIF-1α and inhibition of CXCR4. These results are in accordance with previous reports in different types of cancer (16,46) and suggest that upregulation of CXCR4 by HIF-1α in response to hypoxia plays a biological role in gastric cancer cell migration. We previously reported that functional CXCR4 plays an important role in cancer cell migration during normoxia in gastric and gallbladder cancers (18,21), suggesting that the CXCR4/ CXCL12 axis may be significantly involved in cancer progression and may be a potential target for therapeutics that block the interaction between CXCL12 and CXCR4, or that inhibit downstream signaling, in the treatment of cancer.…”
Section: Discussionsupporting
confidence: 83%
“…Several recent studies provide evidence that hypoxia, primarily acting through HIF-1α, is involved in the upregulation of CXCR4 in carcinomas and hematologic malignancies such as lung, breast cancer and myeloma, with HIF-1α binding directly to the CXCR4 promoter (15,(40)(41)(42)(43)(44)(45). In this study, hypoxia increased CXCR4 protein levels and cell surface expression by activating HIF-1α, thereby supporting previous findings from other cancer cell lines and suggesting that tumor hypoxia plays a crucial role in the regulation of CXCR4 (15,16,41).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Recently, CXCR4 was detected on TICs and mRNA levels were found to be significantly higher in this population in comparison to the non-TICs (44)(45)(46)(47)(48). The upregulation of CXCR4 cell surface expression corresponded to a significant increase in EMT in response to SDF1-α in vitro (64,65). In the present study, CT was shown to down-regulate CXCR4 expression in total LNCaP cells and the TIC population; hence, it is possible CT can further regulate TICs by regulating the CXCR4-SDF1 axis and disrupting its ability to interact with the microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus possible that b7 integrin expression on HSCs may directly regulate CXCR4 cell surface expression and/or reduce its internalization. Alternatively, several reports have shown that exposure to hypoxia led to upregulation of CXCR4 expression in a diverse range of cancer cells [36][37][38][39][40][41][42]. Thus, the surface expression of b7 integrin on HSCs may influence HSC locomotion within a specific BM niche, where low oxygen tension may favor the expression of CXCR4.…”
Section: Discussionmentioning
confidence: 99%